For the interprofessional management of the discomfort of long-term care facility residents with dementia. - Choi, Young-Rim; Lee, Ye-Na; Kim, Da-Yeong; Chang, Sung Ok (Journal of Interprofessional Care)
Educating interprofessional practitioners in long-term care facilities (LTCFs) is critical for managing discomfort of residents with dementia, which is often unnoticed and undertreated. A framework of education on discomfort management that is applicable in various environments in different facilities is necessary. We developed a preliminary framework to educate interprofessional practitioners on discomfort management of dementia residents in LTCFs. We conducted a three-step research process: a literature review using topic modeling, in-depth interviews, and Delphi surveys. We derived four categories for an interprofessional approach toward discomfort management education in LTCFs: identifying visual and nonvisual signs to communicate among professionals, close observation using comparison and contrast to share information for discomfort care, harmony in interprofessional roles, and applying common and specific professional knowledge for discomfort management. The findings provide the first outline for an educational framework for interprofessional discomfort management in LTCFs for residents with dementia. We recommend interventions across different cultures to verify the framework in future research.